Parent-child relationship and aggression among adolescents in Tehran, Iran - Masoumeh, Homauni; Mansor, Mariani; Yaacob, Siti Nor; Abu Talib, Mansor (Marsland Press, 2014)
The purpose of this study was to examine the relationship between parent-child relationship and the adolescent’s aggression among Iranian high schools students in Tehran, Iran. There is a transformation in the parent-child relationship as child approaches adolescence due to biological, cognitive and emotional changes. The present study was carried out among Iranian students. Number of respondents in the present study includes 200 (50%) males and 200 (50%) females from 20 high schools in Tehran, Iran. Respondents were between the ages of 16 to 18 years. Pearson correlation between subscales of aggression and between parent-child relationship was done and according results the strength of correlation between mother-child relation and aggression is moderate but more than Father–childe relation. This means that respondents of low Father and Mother Relation have higher aggressive tendencies.